TRANSFORMASI NON-GOVERNMENT ORGANIZATION: DARI CHARITABLE ORGANIZATION MENJADI SOCIAL BUSINESS STUDI KASUS PADA PUSDAKOTA UBAYA - Bodhiya Wijaya Mulya (CALYPTRA, 2014)
This study try to examine transformation of Non-Government Organization from charitable organization to social business. This research is basic research so it would help to fill research gap in social entrepreneurship research. Researcher use case study method with interview and observation as data collection tools. Finding on this study found that NGO need push to transform. Without this force NGO wouldn’t transform to social business. In this study, researcher also found there are three steps in this transformation. The steps consist of struggle for sustain, searching for identity, and maturity and innovation. The transformation isn’t easy. NGO have to make great effort. There are three impact of transformation. The impact are sustainability, expansion ability, and irregularity managerial.